IMPLEMENTASI KONSELING SEBAYA TERHADAP KEPERCAYAAN DIRI SISWA KORBAN BODY SHAMING DI MTs NEGERI 3 LAHAT - Elsa Anggilena; Taty Fauzi; Endang Surtiyoni (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
Body shaming is a form of verbal bullying, namely an act of belittling or embarrassing someone's physical appearance. This study aims to determine the effect of peer counseling services on increasing the self-confidence of students who are victims of body shaming. The research method used is quantitative, pre- experimental with a one-group pretest and posttest design. Sampling using purpose sampling technique as many as 7 students in class VIII.2 who were victims of body shaming and had a low level of confidence. Data were collected using a pretest posttest and observation questionnaire. Data analysis using the Wilcoxon Sidned Rank test to determine changes before and after treatment was given. The results showed a calculated Z value of -2.360 with an Asymp.sig valueof 0.018 <0.05. So Ha is accepted and Ho is rejected. This shows that peer counseling services are effective in increasing the self-confidence of students who experience body shaming. Thus, the implementation of peer counseling can be used as an effective strategy in helping to overcome the problem of body shaming at MTs Negeri 3 Lahat.